Vegetação e recursos hídricos na Bacia do Rio Claro – Minas Gerais: diagnóstico e instrumentos para a gestão - Sousa, Joyce Silvestre de (2017)
The increase in anthropic pressure over natural resources causes intense environmental impacts, which weakens the potential of nature to offer ecosystemic services. The environmental management, composed by actions of conservation that must point what must be protected, where and how it must be protected, can be subsidized by proposals of indication of prioritary areas for conservation of natural resources. The priorization of these areas can lower the costs of transaction and potentiate the effects of a Project for Payment for Environmental Services (PES). In this context, the general goal of the study is to propose strategies of management of hydric resources and use of the soil in Basin of Rio Claro - MG. As specific goals, it was sought to caracterize the basin related to the hydric resources and its vegetation rates; identify conflicts of use; define prioritary areas for the conservation/preservation that influence the qualitative and quantitative conservation of the hydric resources of the basin; propose the creation of Unities of Conservation; calculate and spatialize the loss of soil in different scenarios; indicate guidelines for the creation of public policies for the incentive of preservation and recovery of the basin by farmers through the PES tool; estimate the values to be collected and gather resources to subsidize the PES.For the evaluation of the dynamics of use and occupation, RapidEye images were used with spatial resolution of 5m, from the year of 2015. The software ArcGis®10.1TM has been used for all of the computational routines. The quantification of the loss of soil has been realized by the RUSLE model. The results show that the basin of Rio Claro has hydric unavailability. The methodologies elaborated in this study have been proved suitable to the mapping of prioritary areas to conservation of water and the proposal of Unities of Conservation. The Unities of Conservation will conserve about 22885 ha among unities of conservation of whole protection and sustainable use. The basin of Rio Claro - MG has characteristics that justify the creation of a PES on its area, like agriculture as predominant use and the existence of conflicts of use in the Areas of Permanent Preservation. The Areas of Conservation of Water (ACWs) and the Unities of Conservation of Water (UCWs) would be a good criterion of eligibility or priority in the application of the resources in a PES, thus securing the goal of qualitative and quantitative conservation of the hydric resources of the area. The estimated environmental benefits provided by the ACWs is the reduction of 84.1% of loss of soil in the basin.